Архитектурный облик Херсонесского святилища раннеэллинистического времени - Жеребцов, Е.Н. (Материалы по археологии, истории и этнографии Таврии, 2005)
Около рубежа V-VI вв. н.э. обветшавшая к тому времени рустованная облицовка круглой эллинистической башни XVI, бывшей первоначально фланговой, была со стороны так называемой римской цитадели укреплена новой кладкой, образовавшей сегментное в плане утолщение башни. В этой кладке были во множестве использованы архитектурные детали нескольких ордерных построек, добытые, видимо, при сносе какого-то одного херсонесского теменоса. Камни были уложены вторично почти без подтески, что обусловило сохранность порезок и раскраски, особенно у повернутых лицевой поверхностью внутрь стены. The characteristics of architectural details of different cultural buildings in Chersonesos of early Hellenistic period are examined in this article. They preserved thanks to the use of walls adjacent to it and in revetment. All the stones were laid for the second time almost without cutting, that stipulated their undamaged state (including colouring, especially of the stones turned their facial side inside). The details were found in 1905 by K. K. Kostsciushko - Valiuzhenich. In accordance with constructive purpose, stylistics and scale the author of the article related the details to several buildings of one architectural complex - sanctuary, which consisted of a large alter situated in the centre of the yard with a fence, inside it there was a monument with a holy image, some treasuries and votives. It is impossible to define which deity it belonged to. Perhaps, it was a part of a large public religious centre of Chersonesos.